Solubilized Amnion Membrane Hyaluronic Acid Hydrogel Accelerates Full-Thickness Wound Healing. (23rd September 2017) - Murphy, Sean V.; Skardal, Aleksander; Song, Lujie; Sutton, Khiry; Haug, Rebecca; Mack, David L.; Jackson, John; Soker, Shay; Atala, Anthony
Abstract: The early and effective treatment of wounds is vital to ensure proper wound closure and healing with appropriate functional and cosmetic outcomes. The use of human amnion membranes for wound care has been shown to be safe and effective. However, the difficulty in handling and placing thin sheets of membrane, and the high costs associated with the use of living cellularized tissue has limited the clinical application of amniotic membrane wound healing products. Here, we describe a novel amnion membrane-derived product, processed to result in a cell-free solution, while maintaining high concentrations of cell-derived cytokines and growth factors. The solubilized amnion membrane (SAM) combined with the carrier hyaluronic acid (HA) hydrogel (HA-SAM) is easy to produce, store, and apply to wounds. We demonstrated the efficacy of HA-SAM as a wound treatment using a full-thickness murine wound model. HA-SAM significantly accelerated wound closure through re-epithelialization and prevented wound contraction. HA-SAM-treated wounds had thicker regenerated skin, increased total number of blood vessels, and greater numbers of proliferating keratinocytes within the epidermis. Overall, this study confirms the efficacy of the amnion membrane as a wound treatment/dressing, and overcomes many of the limitations associated with using fresh, cryopreserved, or dehydrated tissue by providing a hydrogel delivery system for SAM. Abstract : Time-course images from in vivo wound healing study. A 2 × 2 cm full-thickness wound was created on the back of nude mice and received one of three treatment options; (A) : Untreated other than standard bandaging; (B) : HA-gel only or; (C) : HA-SAM gel.